Peningkatan Hasil Belajar IPAS pada Siswa Kelas IV melalui Pembelajaran Berbasis Masalah di SD Negeri Perintis B : Penelitian - Alvi Febrianti Putri Utami; Sherly Anatasya Ruswandi; Rinaldi Yusup (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve the learning outcomes of fourth grade students in the subject of Natural and Social Sciences (IPAS) through the application of problem-based learning (PBL) models at SD Perintis B. The method used is classroom action research (PTK) which is carried out in two cycles. Data were collected through pre-test, post-test, observation of student activities, and motivation questionnaires. The results of the study showed that the application of PBL can improve student learning outcomes, with the average post-test score increasing significantly compared to the pre-test. In addition, student involvement in the learning process also increased, with 80% of students actively participating in group discussions. This study provides empirical evidence that the problem-based learning model is effective in improving students' understanding of the IPAS material and can be used as an alternative to a more interactive teaching method. These findings are expected to provide a positive contribution to the development of learning methods in elementary schools.